The acute effects of post-activation potentiation on sport-climbing specific power exercises - Krzysztof Sas-Nowosielski; Klaudia Angelika Kandzia (Kazimierz Wielki University, 2018)
The effect of performing biomechanically similar exercises in such order that resistance exercise was followed by plyometric, power or speed exercise is a temporal increase in power and force production. The physiological rationale for complex training effectiveness is a phenomenon known as post-activation potentiation (PAP). Only a few studies were dedicated to various aspects of sport climbers' training and to our knowledge, no study has examined the effects of post-activation potentiation and/or complex training in climbing. The purpose of this study was to determine if there was a performance-enhancing response of power and power endurance exercises on the campus board that were performed after a high-load resistance exercise (weighted pull-ups). 12 climbers participated in the study. During the first testing condition, climbers were asked to hang on the lowest rung and perform three maximal reaches with their dominant arm, separated with 10 s rest periods. The second test involved touches to the rung just below climbers' maximal reach, then coming back down to the bottom rung, and performing the same exercise with the second hand. The climbers were required to repeat this cycle as many times as possible in the 20 s period. After 10 min rest, climbers repeated both tests after preloading. The time interval between resistance exercise (weighted pull ups) and campus power or power endurance exercise was 4 minutes. On average during the test of maximal reach after weighted pull-ups, climbers improved their performance on the campus board by 3.11 cm. The difference between PRE and POST loading was statistically significant. The best of the reaches performed in the set was 2.23 cm higher after preloading. In the power endurance ("Touches") test, only a tendency toward difference between the number of reaches in baseline and after heavy resistance exercise was observed, although the effect size suggests moderate strength of the relationship between both conditions, The results indicate positive effect of weighted pull-up exercise on subsequent power exercises on the campus board. It should be noted, however, that results of the preload on campus board exercise varied between individuals and more studies are needed in order to determine the most effective protocol of pairs of exercises in sport climbers' training.